Insights Into the Experiences of People Living With Chronic Kidney Disease and Obesity Participating in a Randomized Controlled Weight Loss Trial: A Qualitative Study - Marguerite Conley; Nicole Scholes-Robertson; Soraya Cunningham; Hannah L. Mayr; Kirsten Hepburn; David W. Mudge; Justin Holland; Tammy Tonges; David W. Johnson; Andrea K. Viecelli; Helen L. MacLaughlin (Journal of the Academy of Nutrition and Dietetics, 2026)

Bioaccumulation of trace elements by Leach's storm-petrels (Hydrobates leucorhous) in the North and South Atlantic Ocean during the non-breeding period - Catherine Potvin; Manon Sorais; Robert A. Ronconi; Katharine R. Studholme; April Hedd; Alexander L. Bond; Vegard S. Bråthen; Sydney M. Collins; Laura Crick; Joshua T. Cunningham; Anne N.M.A. Ausems; David A. Fifield; et al. (Marine Pollution Bulletin, 2026)

A cloud-based JupyterHub platform for community research with the NextGen water resources modeling framework - Ayman Nassar; David G. Tarboton; Furqan Baig; Josh Cunningham; Arpita Patel; James Halgren; Benjamin Lee; Homa Salehabadi; Anthony M. Castronova; Irene Garousi-Nejad (Environmental Modelling & Software, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Bovine milk glycoproteins concentration influences bacterial growth and anti-pathogenic bioactivities relevant to the infant gut in vitro - Iwona Dziembała-Gładysz; Marie Le Berre; Stephen Cunningham; Laura Walsh; Uthesh Umapathy; Yousef Joubran; Gerard T.A. Fleming; David A. Goulding; Lokesh Joshi; Jonathan O'Regan; Michelle Kilcoyne (International Dairy Journal, 2026)

Blood–Brain Barrier Permeability in Cases of Post-operative Delirium Is Associated with Central Nervous System Phosphatidylcholine Imbalances - Mijin Jung; Xiaobei Pan; Aoife Sweeney; Anthony P. Passmore; Bernadette McGuinness; Daniel F. McAuley; David Beverland; Amanda J. Heslegrave; Jonathan Schott; Henrik Zetterberg; Emma L. Cunningham; Brian D. Green (Molecular Neurobiology, 2026)
Blood-brain barrier (BBB) permeability is reportedly increased in patients exhibiting postoperative delirium. Changes in either cerebrospinal fluid (CSF) or blood metabolites have also been reported in cases of delirium. This investigation examined whether BBB permeability influences metabolite concentrations on either side of the barrier, and whether this changes in cases of delirium. This study is a nested case-control cohort ( n = 54) drawn from the entire cohort of n = 315 participants. Preoperative CSF and plasma from postoperative delirium and control participants matched for age and gender underwent metabolomic profiling. Concentrations of metabolites in plasma and in CSF were obtained, and where measurable, a CSF/plasma metabolite ratio (Qmetab) was calculated. CSF/plasma albumin ratio (Qalb), a recognized indicator of BBB permeability, was also calculated. The above parameters were compared between delirium and control groups. Finally, each Qmetab was correlated against Qalb for control or delirium cases. In cases where delirium would later occur there were significant elevations in the Qmetabs of amino acids (Gln, His, Met, Phe, Tyr and Val), and one phosphatidylcholine (PC). Many other PC Qmetabs significantly correlated with Qalb and this mainly occurred in individuals subsequently experiencing delirium. In persons prone to postoperative delirium, the equilibrium of certain species of PC across the BBB correlates with BBB permeability. It is unclear whether this occurs because of changes in PC metabolism or transit, but understanding this could improve our understanding of the mechanisms underlying delirium.

Assessing structural resilience of masonry chamber-housed substations subject to flood flow and debris impact - Wenzhu Li; Lee S. Cunningham; David M. Schultz; Sarah Mander; Chin Kim Gan; Mathaios Panteli (Innovative Infrastructure Solutions, 2025)
Chamber-housed substations are a common substation type, essential for voltage regulation, load balancing, and fault isolation to ensure power supply grid stability and reliability. As typically ground-based structures, chamber-housed substations are vulnerable to damage from flooding. In the case of chambers constructed from plain masonry, these may be susceptible to structural damage from forces generated by flood flows. Although previous studies have examined substation failures based on flood levels, they often overlook the structural damage caused by moving floodwaters and floating debris, thereby underestimating risks and overestimating substation resilience. The present study introduces an analytical framework that uses computational fluid dynamics (CFD) coupled with finite element (FE) analysis to predict flood forces and structural responses in a level of detail that would hitherto not be possible with existing design code approaches. The CFD-based modelling approach was validated against existing hydraulic experiments and subsequently applied to a case study of a typical masonry chamber-housed substation in Malaysia, a country prone to severe annual flooding. The results reveal that substation walls can withstand flood velocities up to 10 m/s without debris. However, the presence of debris leads to damage at velocities below 2 m/s, highlighting a significant reduction in resilience. Fragility and risk curves, derived from a normalised Weibull function, further reveal that ignoring debris impact underestimates forces on walls by 60% to 83%. These findings highlight the need to update design guidelines to account for debris impact and to develop suitable retrofitting strategies for existing chambers.

Design of a vectorized rubidium scalar magnetometer for SmallSat applications - Carolina T. Chism; Robert A. Marshall; Aldo Aguilar-Nadalini; Svenja Knappe; David Malaspina; K. Jeramy Hughes; Michaela Ellmeier; Sebastian Wankmueller; Conor Cunningham; Tyler Maydew; Orang Alem (Advances in Space Research, 2025)

Apex Scavenger Declines Have Cascading Effects on Soil Biogeochemistry and Ecosystem Processes - Torrey Stephenson; David W. Crowder; Ernest Osburn; Michael Strickland; Menna Jones; Savannah Bartel; Kawinwit Kittipalawattanapol; Calum X. Cunningham; Tara Hudiburg; Andrew Storfer; Julia Piaskowski; Laurel Lynch (Global Change Biology, 2025)
Global apex scavenger declines strongly alter food web dynamics, but studies rarely test whether trophic downgrading impacts ecosystem functions. Here, we leverage a unique, disease‐induced gradient in Tasmanian devil ( Sarcophilus harrisii ) population densities to assess feedbacks between carcass persistence, subordinate scavenger guilds, and biogeochemical cycling. We further explored interkingdom and seasonal interactions by manipulating carcass access and replicating experiments in warmer, drier summer versus cooler, wetter winter periods. We show Tasmanian devil declines significantly extend carcass persistence and increase the flux of carcass‐derived nutrients belowground (e.g., by 18–134‐fold for ammonium). Greater nutrient availability reduces soil microbiome diversity by up to 26%, increasing the relative abundance of putative zoonotic pathogens. Nutrient subsidies also shift microbial communities toward faster‐growing taxa that invest less energy in resource acquisition, with implications for soil carbon sequestration. Rates of carcass decomposition were reduced in the winter, dampening soil biogeochemical responses and interkingdom competition. Notably, while less efficient scavenger guilds clearly facilitate carcass consumption, they were not able to fill the functional role of apex scavengers. Our study illustrates how trophic downgrading effects can ripple across all levels of ecological organization.

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Evaluating the performance of a system model in predicting zooplankton dynamics: Insights from the Bering Sea ecosystem - Genoa Sullaway; Curry J. Cunningham; David Kimmel; Darren J. Pilcher; James T. Thorson (Fisheries Oceanography, 2025)
Understanding how ecosystem change influences fishery resources through trophic pathways is a key tenet of ecosystem‐based fishery management. System models (SM), which use numerical modeling to describe physical and biological processes, can advance inclusion of ecosystem and prey information in fisheries management; however, incorporating SMs in management requires evaluation against empirical data. The Bering Ecosystem Study Nutrient‐Phytoplankton‐Zooplankton (BESTNPZ) model is an SM (originally created by the Bering Ecosystem Study, which initiated in 2006 and was expanded by Kearney et al.) includes zooplankton biomass hindcasts for the Bering Sea. In the Bering Sea, zooplankton are an important prey item for fishery species, yet the zooplankton component of this SM has not been validated against empirical data. We compared empirical zooplankton data to BESTNPZ hindcast estimates for three zooplankton functional groups and found that the two sources of information are on different absolute scales. We found high correlation between relative seasonal biomass trends estimated by BESTNPZ and empirical data for large off‐shelf copepods ( Neocalanus spp.) and low correlations for large on‐shelf copepods and small copepods ( Calanus spp. and Pseudocalanus spp., respectively). To address these discrepancies, we constructed hybrid species distribution models (H‐SDM), which predict zooplankton biomass using the BESTNPZ hindcast and environmental covariates. We found that H‐SDMs offered marginal improvements over correlative species distribution models (C‐SDMs) relying solely on empirical data for spatial extrapolation and little improvement for most functional groups when forecasting short‐term temporal zooplankton biomass trends. Overall, we suggest that interpretation of current BESTNPZ hindcasts should be tempered by our understanding of key mismatches in absolute scale, seasonality, and annual indices between BESTNPZ and empirical data.

Identification of novel microcystins in algal extracts by a liquid chromatography–high-resolution mass spectrometry data analysis pipeline - Kirsten A. Cottrill; Christopher O. Miles; Logan C. Krajewski; Brady R. Cunningham; William Bragg; Noelani R. Boise; Kristin D. Victry; David S. Wunschel; Karen L. Wahl; Elizabeth I. Hamelin (Harmful Algae, 2024)

The BirdLife Seabird Tracking Database: 20 years of collaboration for marine conservation - Ana P.B. Carneiro; Maria P. Dias; Bethany L. Clark; Elizabeth J. Pearmain; Jonathan Handley; Amy R. Hodgson; John P. Croxall; Richard A. Phillips; Steffen Oppel; Joanne M. Morten; Ben Lascelles; Cleo Cunningham; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Temporal dynamics of Devonian reef communities: Insights into natural phase shifts and long-term resilience in the face of environmental variability - Amanda Godbold; Nina Clark; Emer T. Cunningham; David J. Bottjer; John M. Pandolfi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Intensive professional vehicle-based shooting provides local control of invasive rusa deer in a peri-urban landscape - Sebastien Comte; Andrew J. Bengsen; Calum X. Cunningham; Michelle Dawson; Anthony R. Pople; David M. Forsyth (Biological Invasions, 2024)
Non-native deer are becoming increasingly common in peri-urban landscapes, where they pose a risk to the health and wellbeing of people. Professional vehicle-based shooting is commonly used to control deer populations in these complex landscapes, but the effectiveness and cost of this method have seldom been evaluated. We analyzed the effectiveness and cost of using professional vehicle-based shooting to reduce the abundance and impacts of non-native rusa deer ( Cervus timorensis ) in a peri-urban landscape in Wollongong, eastern Australia, during 2011–2021. We incorporated the results from an independent monitoring program into a Bayesian joint-likelihood framework to model spatio-temporal changes in rusa deer abundance. Finally, we used our findings to assess the effect of the management program on the number of complaints from the residents. After eleven years and the removal of 4701 rusa deer from Wollongong LGA (712 km 2 ), deer abundance did not change in 74.7% of the area, decreased in 19.4% of the area (mostly in and around the sites where the professional shooting occurred), and increased in 5.9% of the area. Shooting was most cost-effective during winter when the longer hours of darkness meant that shooters could visit more sites. In contrast to deer abundance, the probability of residents complaining about deer increased in space and time. Our study shows that professional vehicle-based shooting can locally reduce the abundance of invasive deer in a peri-urban landscape, providing that sufficient control effort is expended. We suggest that shooting effort is currently too thinly spread across this peri-urban landscape, and that concentrating shooting effort on the areas of greatest deer abundance and resident complaints might be a more cost-effective strategy for managing invasive deer in peri-urban landscapes.

Open-cup nesters in the Kalahari: Incubation and egg-shading behaviour in passerines cannot be detected with temperature dataloggers during hot periods - David Diez-Méndez; Susan J. Cunningham (Journal of Arid Environments, 2024)

Reasons for meal termination, eating frequency, and typical meal context differ between persons with and without a spinal cord injury - Gary J. Farkas; Paige M. Cunningham; Alicia M. Sneij; John E. Hayes; Mark S. Nash; Arthur S. Berg; David R. Gater; Barbara J. Rolls (Appetite, 2024)

Pyrogeography in flux: Reorganization of Australian fire regimes in a hotter world - Calum X. Cunningham; Grant J. Williamson; Rachael H. Nolan; Lina Teckentrup; Matthias M. Boer; David M. J. S. Bowman (Global Change Biology, 2024)
Changes to the spatiotemporal patterns of wildfire are having profound implications for ecosystems and society globally, but we have limited understanding of the extent to which fire regimes will reorganize in a warming world. While predicting regime shifts remains challenging because of complex climate–vegetation–fire feedbacks, understanding the climate niches of fire regimes provides a simple way to identify locations most at risk of regime change. Using globally available satellite datasets, we constructed 14 metrics describing the spatiotemporal dimensions of fire and then delineated Australia's pyroregions—the geographic area encapsulating a broad fire regime. Cluster analysis revealed 18 pyroregions, notably including the (1) high‐intensity, infrequent fires of the temperate forests, (2) high‐frequency, smaller fires of the tropical savanna, and (3) low‐intensity, diurnal, human‐engineered fires of the agricultural zones. To inform the risk of regime shifts, we identified locations where the climate under three CMIP6 scenarios is projected to shift (i) beyond each pyroregion's historical climate niche, and (ii) into climate space that is novel to the Australian continent. Under middle‐of‐the‐road climate projections (SSP2‐4.5), an average of 65% of the extent of the pyroregions occurred beyond their historical climate niches by 2081–2100. Further, 52% of pyroregion extents, on average, were projected to occur in climate space without present‐day analogues on the Australian continent, implying high risk of shifting to states that also lack present‐day counterparts. Pyroregions in tropical and hot‐arid climates were most at risk of shifting into both locally and continentally novel climate space because (i) their niches are narrower than southern temperate pyroregions, and (ii) their already‐hot climates lead to earlier departure from present‐day climate space. Such a shift implies widespread risk of regime shifts and the emergence of no‐analogue fire regimes. Our approach can be applied to other regions to assess vulnerability to rapid fire regime change.

Factors influencing mercury exposure in Arctic-breeding shorebirds - Marie Perkins; Iain J. Stenhouse; Richard B. Lanctot; Stephen Brown; Joël Bêty; Megan Boldenow; Jenny Cunningham; Willow English; River Gates; H. Grant Gilchrist; Marie-Andrée Giroux; Kirsten Grond; et al. (Ecotoxicology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Comparison Between Ground, Helicopter, and Unmanned Aircraft System Magnetic Datasets: A Case Study from the Abitibi Greenstone Belt, Canada - Michael Cunningham; Claire Samson; Jeremy Laliberté; Mark Goldie; Alan Wood; David Birkett (Pure and Applied Geophysics, 2022)

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Heat increases full-length SMN splicing: promise for splice-augmenting therapies for SMA - Catherine E. Dominguez; David Cunningham; Akila S. Venkataramany; Dawn S. Chandler (Human Genetics, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Examining the Role of Marine Mammals and Seabirds in Southeast Alaska’s Marine Ecosystem Dynamics - Melissa Rhodes-Reese; David Clay; Curry Cunningham; Janet Moriles-Miller; Cheryl Reese; Joe Roman; Joseph D. Warren; Heidi C. Pearson (Frontiers in Marine Science, 2021)
Primary producers are the foundation of marine food webs and require reliable nutrient sources to maintain their important role with ecosystems. While marine mammals and seabirds can play critical roles in marine nutrient cycling, their contributions are often overlooked. Southeast Alaska’s marine environment supports abundant marine mammal and seabird populations in addition to valuable fisheries. Nonetheless, there is still relatively little known about nutrient sources and fluxes in this region which is a critical component of fisheries management. The goal of our study was to advance knowledge of the role of mammals and seabirds in marine nutrient cycling and to understand how changing marine mammal and seabird populations may alter ecosystem dynamics. We utilized qualitative network models (QNMs) to examine how a simulated Southeast Alaska ecosystem would respond to an increase in marine mammals, seabirds, and nutrients. Researchers are increasingly utilizing QNMs as a first step in the development of ecosystem-based fisheries management plans as their adaptable nature is well suited to address rapidly changing climatic conditions. Our results indicate that marine mammals and seabirds make important contributions to marine nutrient concentrations in the region and that these valuable ecosystem services should not be overlooked.

Climate-Relevant Ocean Transport Measurements in the Atlantic and Arctic Oceans - Barbara Berx; Denis Volkov; Johanna Baehr; Molly Baringer; Peter Brandt; Kristin Burmeister; Stuart Cunningham; Marieke de Jong; Laura de Steur; Shenfu Dong; Eleanor Frajka-Williams; Gustavo Goni; et al. (Oceanography, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Measurement error and reliability of TMS metrics collected from biceps and triceps in individuals with chronic incomplete tetraplegia - Tarun Arora; Kelsey Potter-Baker; Kyle O’Laughlin; Manshi Li; Xiaofeng Wang; David Cunningham; Francois Bethoux; Frederick Frost; Ela B. Plow (Experimental Brain Research, 2021)

Quantifying 25 years of disease‐caused declines in Tasmanian devil populations: host density drives spatial pathogen spread - Calum X. Cunningham; Sebastien Comte; Hamish McCallum; David G. Hamilton; Rodrigo Hamede; Andrew Storfer; Tracey Hollings; Manuel Ruiz‐Aravena; Douglas H. Kerlin; Barry W. Brook; Greg Hocking; Manna E. Jones (Ecology Letters, 2021)
Infectious diseases are strong drivers of wildlife population dynamics, however, empirical analyses from the early stages of pathogen emergence are rare. Tasmanian devil facial tumour disease (DFTD), discovered in 1996, provides the opportunity to study an epizootic from its inception. We use a pattern‐oriented diffusion simulation to model the spatial spread of DFTD across the species' range and quantify population effects by jointly modelling multiple streams of data spanning 35 years. We estimate the wild devil population peaked at 53 000 in 1996, less than half of previous estimates. DFTD spread rapidly through high‐density areas, with spread velocity slowing in areas of low host densities. By 2020, DFTD occupied >90% of the species' range, causing 82% declines in local densities and reducing the total population to 16 900. Encouragingly, our model forecasts the population decline should level‐off within the next decade, supporting conservation management focused on facilitating evolution of resistance and tolerance.

Inversion of Magnetic Data Acquired with a Rotary-Wing Unmanned Aircraft System for Gold Exploration - Michael Cunningham; Claire Samson; Jeremy Laliberté; Mark Goldie; Alan Wood; David Birkett (Pure and Applied Geophysics, 2021)

Behavioral effects of benzylideneoxymorphone (BOM), a low efficacy µ opioid receptor agonist and a δ opioid receptor antagonist - Sanjana Mada; Lisa R. Gerak; Amélie Soyer; David R. Maguire; Zehua Hu; Vanessa Minervini; Christopher W. Cunningham; Charles P. France (Psychopharmacology, 2020)

A genome-wide association study implicates the BMP7 locus as a risk factor for nonsyndromic metopic craniosynostosis - Cristina M. Justice; Araceli Cuellar; Krithi Bala; Jeremy A. Sabourin; Michael L. Cunningham; Karen Crawford; Julie M. Phipps; Yan Zhou; Deirdre Cilliers; Jo C. Byren; David Johnson; Steven A. Wall; et al. (Human Genetics, 2020)

Uses for humanised mouse models in precision medicine for neurodegenerative disease - Remya R. Nair; Silvia Corrochano; Samanta Gasco; Charlotte Tibbit; David Thompson; Cheryl Maduro; Zeinab Ali; Pietro Fratta; Abraham Acevedo Arozena; Thomas J. Cunningham; Elizabeth M. C. Fisher (Mammalian Genome, 2019)
Neurodegenerative disease encompasses a wide range of disorders afflicting the central and peripheral nervous systems and is a major unmet biomedical need of our time. There are very limited treatments, and no cures, for most of these diseases, including Alzheimer’s Disease, Parkinson's Disease, Huntington Disease, and Motor Neuron Diseases. Mouse and other animal models provide hope by analysing them to understand pathogenic mechanisms, to identify drug targets, and to develop gene therapies and stem cell therapies. However, despite many decades of research, virtually no new treatments have reached the clinic. Increasingly, it is apparent that human heterogeneity within clinically defined neurodegenerative disorders, and between patients with the same genetic mutations, significantly impacts disease presentation and, potentially, therapeutic efficacy. Therefore, stratifying patients according to genetics, lifestyle, disease presentation, ethnicity, and other parameters may hold the key to bringing effective therapies from the bench to the clinic. Here, we discuss genetic and cellular humanised mouse models, and how they help in defining the genetic and environmental parameters associated with neurodegenerative disease, and so help in developing effective precision medicine strategies for future healthcare.

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Cephalopod component of Snares Penguin (Eudyptes robustus) at Snares Islands, New Zealand in the 1980´s: relationships with local fisheries and implications on the penguin’s conservation - Hugo Guímaro; David Thompson; Vitor Paiva; Duncan Cunningham; Philip Moors; José Xavier (Frontiers in Marine Science, 2019)

Topical Drug Delivery to the Posterior Segment of the Eye: Addressing the Challenge of Preclinical to Clinical Translation - Gerard A. Rodrigues; David Lutz; Jie Shen; Xiaoda Yuan; Hong Shen; James Cunningham; Hongwen M. Rivers (Pharmaceutical Research, 2018)

SMN regulation in SMA and in response to stress: new paradigms and therapeutic possibilities - Catherine E. Dominguez; David Cunningham; Dawn S. Chandler (Human Genetics, 2017)

The effect of motor overflow on bimanual asymmetric force coordination - David A. Cunningham; Sarah M. Roelle; Didier Allexandre; Kelsey A. Potter-Baker; Vishwanath Sankarasubramanian; Jayme S. Knutson; Guang H. Yue; Andre G. Machado; Ela B. Plow (Experimental Brain Research, 2017)

Effects of past and present livestock grazing on herpetofauna in a landscape‐scale experiment - Geoffrey M. Kay; Alessio Mortelliti; Ayesha Tulloch; Philip Barton; Daniel Florance; Saul A. Cunningham; David B. Lindenmayer (Conservation Biology, 2017)
Livestock grazing is the most widespread land use on Earth and can have negative effects on biodiversity. Yet, many of the mechanisms by which grazing leads to changes in biodiversity remain unresolved. One reason is that conventional grazing studies often target broad treatments rather than specific parameters of grazing (e.g., intensity, duration, and frequency) or fail to account for historical grazing effects. We conducted a landscape‐scale replicated grazing experiment (15,000 km 2 , 97 sites) to examine the impact of past grazing management and current grazing regimes (intensity, duration, and frequency) on a community of ground‐dwelling herpetofauna (39 species). We analyzed community variables (species richness and composition) for all species and built multiseason patch‐occupancy models to predict local colonization and extinction for the 7 most abundant species. Past grazing practices did not influence community richness but did affect community composition and patch colonization and extinction for 4 of 7 species. Present grazing parameters did not influence community richness or composition, but 6 of the 7 target species were affected by at least one grazing parameter. Grazing frequency had the most consistent influence, positively affecting 3 of 7 species (increased colonization or decreased extinction). Past grazing practice affected community composition and population dynamics in some species in different ways, which suggests that conservation planners should examine the different grazing histories of an area. Species responded differently to specific current grazing practices; thus, incentive programs that apply a diversity of approaches rather than focusing on a change such as reduced grazing intensity should be considered. Based on our findings, we suggest that determining fine‐scale grazing attributes is essential for advancing grazing as a conservation strategy.

Approaches to Landscape Scale Inference and Study Design - Ross B. Cunningham; David B. Lindenmayer (Current Landscape Ecology Reports, 2017)

Network analysis of host–virus communities in bats and rodents reveals determinants of cross‐species transmission - Angela D. Luis; Thomas J. O'Shea; David T. S. Hayman; James L. N. Wood; Andrew A. Cunningham; Amy T. Gilbert; James N. Mills; Colleen T. Webb (Ecology Letters, 2015)
Bats are natural reservoirs of several important emerging viruses. Cross‐species transmission appears to be quite common among bats, which may contribute to their unique reservoir potential. Therefore, understanding the importance of bats as reservoirs requires examining them in a community context rather than concentrating on individual species. Here, we use a network approach to identify ecological and biological correlates of cross‐species virus transmission in bats and rodents, another important host group. We show that given our current knowledge the bat viral sharing network is more connected than the rodent network, suggesting viruses may pass more easily between bat species. We identify host traits associated with important reservoir species: gregarious bats are more likely to share more viruses and bats which migrate regionally are important for spreading viruses through the network. We identify multiple communities of viral sharing within bats and rodents and highlight potential species traits that can help guide studies of novel pathogen emergence.

Cell adhesion properties of neural stem cells in the chick embryo - David R. Canning; Rebecca L. Cunningham (In Vitro Cellular & Developmental Biology - Animal, 2015)

Public concerns regarding the storage and secondary uses of residual newborn bloodspots: an analysis of print media, legal cases, and public engagement activities - Shannon Cunningham; Kieran C. O’Doherty; Karine Sénécal; David Secko; Denise Avard (Journal of Community Genetics, 2015)

The Lived Experience of Low Back Pain Among Irish Farmers: Case Studies - Aoife Osborne; Catherine Blake; David Meredith; John McNamara; Jim Phelan; Caitriona Cunningham (Journal of Agromedicine, 2014)

The role of carrion in maintaining biodiversity and ecological processes in terrestrial ecosystems - Philip S. Barton; Saul A. Cunningham; David B. Lindenmayer; Adrian D. Manning (Oecologia, 2013)

Model‐guided fieldwork: practical guidelines for multidisciplinary research on wildlife ecological and epidemiological dynamics - Olivier Restif; David T. S. Hayman; Juliet R. C. Pulliam; Raina K. Plowright; Dylan B. George; Angela D. Luis; Andrew A. Cunningham; Richard A. Bowen; Anthony R. Fooks; Thomas J. O'Shea; James L. N. Wood; Colleen T. Webb (Ecology Letters, 2012)
Infectious disease ecology has recently raised its public profile beyond the scientific community due to the major threats that wildlife infections pose to biological conservation, animal welfare, human health and food security. As we start unravelling the full extent of emerging infectious diseases, there is an urgent need to facilitate multidisciplinary research in this area. Even though research in ecology has always had a strong theoretical component, cultural and technical hurdles often hamper direct collaboration between theoreticians and empiricists. Building upon our collective experience of multidisciplinary research and teaching in this area, we propose practical guidelines to help with effective integration among mathematical modelling, fieldwork and laboratory work. Modelling tools can be used at all steps of a field‐based research programme, from the formulation of working hypotheses to field study design and data analysis. We illustrate our model‐guided fieldwork framework with two case studies we have been conducting on wildlife infectious diseases: plague transmission in prairie dogs and lyssavirus dynamics in A merican and A frican bats. These demonstrate that mechanistic models, if properly integrated in research programmes, can provide a framework for holistic approaches to complex biological systems.

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Fine‐scale heterogeneity in beetle assemblages under co‐occurring Eucalyptus in the same subgenus - Philip S. Barton; Adrian D. Manning; Heloise Gibb; David B. Lindenmayer; Saul A. Cunningham (Journal of Biogeography, 2010)
Aim Insect biodiversity is often positively associated with habitat heterogeneity. However, this relationship depends on spatial scale, with most studies focused on differences between habitats at large scales with a variety of forest tree species. We examined fine‐scale heterogeneity in ground‐dwelling beetle assemblages under co‐occurring trees in the same subgenus: Eucalyptus melliodora A. Cunn. ex Schauer and E. blakelyi Maiden (Myrtaceae). Location Critically endangered grassy woodland near Canberra, south‐eastern Australia. Methods We used pitfall traps and Tullgren funnels to sample ground‐dwelling beetles from the litter environment under 47 trees, and examined differences in diversity and composition at spatial scales ranging from 100 to 1000 m. Results Beetle assemblages under the two tree species had distinctive differences in diversity and composition. We found that E. melliodora supported a higher richness and abundance of beetles, but had higher compositional similarity among samples. In contrast, E. blakelyi had a lower abundance and species richness of beetles, but more variability in species composition among samples. Main conclusions Our study shows that heterogeneity in litter habitat under co‐occurring and closely related eucalypt species can influence beetle assemblages at spatial scales of just hundreds of metres. The differential contribution to fine‐scale alpha and beta diversity by each eucalypt can be exploited for conservation purposes by ensuring an appropriate mix of the two species in the temperate woodlands where they co‐occur. This would help not only to maximize biodiversity at landscape scales, but also to maintain heterogeneity in species richness, trophic function and biomass at fine spatial scales.

Characterization of microsatellite loci in the straw-colored fruit bat, Eidolon helvum (Pteropodidae) - Alison J. Peel; Stephen J. Rossiter; James L. N. Wood; Andrew A. Cunningham; David R. Sargan (Conservation Genetics Resources, 2010)

The Combined Effects of Remnant Vegetation and Tree Planting on Farmland Birds - ROSS B. CUNNINGHAM; DAVID B. LINDENMAYER; MASON CRANE; DAMIAN MICHAEL; CHRISTOPHER MacGREGOR; REBECCA MONTAGUE‐DRAKE; JOERN FISCHER (Conservation Biology, 2008)
Biodiversity conservation on agricultural land is a major issue worldwide. We estimated separate and joint effects of remnant native woodland vegetation and recent tree plantings on birds on farms (approximately 500–1000 ha) in the heavily cleared wheat and sheep belt of southern Australia. Much of the variation (>70%) in bird responses was explained by 3 factors: remnant native‐vegetation attributes (native grassland, scattered paddock trees, patches of remnant native woodland); presence or absence of planted native trees; and the size and shape of tree plantings. In terms of the number of species, remnant native vegetation was more important than tree planting, in a 3:1 ratio, approximately. Farms with high values for remnant native vegetation were those most likely to support declining or vulnerable species, although some individual species of conservation concern occurred on farms with large plantings. Farm management for improved bird conservation should account for the cumulative and complementary contributions of many components of remnant native‐vegetation cover (e.g., scattered paddock trees and fallen timber) as well as areas of restored native vegetation.

A cDNA Microarray for Crassostrea virginica and C. gigas - Matthew J. Jenny; Robert W. Chapman; Annalaura Mancia; Yian A. Chen; David J. McKillen; Hal Trent; Paul Lang; Jean-Michel Escoubas; Evelyne Bachere; Viviane Boulo; Z. John Liu; Paul S. Gross; et al. (Marine Biotechnology, 2007)

Fast life cycle assessment of synthetic chemistry (FLASC™) tool - Alan D. Curzons; Concepción Jiménez-González; Ailsa L. Duncan; David J. C. Constable; Virginia L. Cunningham (The International Journal of Life Cycle Assessment, 2007)

Fast life cycle assessment of synthetic chemistry (FLASC™) tool - Alan D. Curzons; Concepción Jiménez-González; Ailsa L. Duncan; David J. C. Constable; Virginia L. Cunningham (The International Journal of Life Cycle Assessment, 2007)

Phylogenetic Analysis of the DNA Polymerase Gene of a Novel Alphaherpesvirus Isolated from an Indian Gyps Vulture - Maria Cardoso; Alex Hyatt; Paul Selleck; Sue Lowther; Vibhu Prakash; Deborah Pain; Andrew A. Cunningham; David Boyle (Virus Genes, 2005)

Hydrothermal vent gastropods from the same family (Provannidae) harbour ɛ‐ and γ‐proteobacterial endosymbionts - Hidetoshi Urakawa; Nicole Dubilier; Yoshihiro Fujiwara; Dale E. Cunningham; Shigeaki Kojima; David A. Stahl (Environmental Microbiology, 2005)
Summary The discovery of new hydrothermal vent systems in the back‐arc basins of the Western Pacific revealed chemosynthesis‐based faunal communities distinct from those of other vents. These vents are dominated by two related gastropods ( Alviniconcha spp. and Ifremeria nautilei ) that harbour symbiotic bacteria in their gills. We used comparative 16S ribosomal RNA (rRNA) gene sequencing and in situ hybridization with rRNA‐targeted probes to characterize the bacterial symbionts of Alviniconcha sp. and I. nautilei from the Manus Basin in the Western Pacific. The analyses revealed that these two gastropod species, although affiliated with the same family, harbour phylogenetically distant chemosymbionts, suggesting independent origins of these endosymbioses. The I. nautilei endosymbiont clusters with sulfur‐oxidizing bacteria within the γ‐Proteobacteria, as is the case for all previously characterized endosymbionts from a wide diversity of host taxa harbouring thioautotrophic prokaryotes. In contrast, the Alviniconcha endosymbiont is affiliated with sulfur‐oxidizing bacteria within the ɛ‐Proteobacteria. These results show that bacteria from the ɛ‐Proteobacteria are also capable of forming endosymbiotic associations with marine invertebrates from chemosynthetic environments. More generally, the endosymbiotic lifestyle is now shown to be distributed throughout all recognized classes of the Proteobacteria.

Role of the serotonin 5-HT2A receptor in the hyperlocomotive and hyperthermic effects of (+)-3,4-methylenedioxymethamphetamine - David V. Herin; Shijing Liu; Thomas Ullrich; Kenner C. Rice; Kathryn A. Cunningham (Psychopharmacology, 2005)

Expanding GSK?s Solvent Selection Guide?application of life cycle assessment to enhance solvent selections - Concepcin Jimnez-Gonzlez; Alan D. Curzons; David J. C. Constable; Virginia L. Cunningham (Clean Technologies and Environmental Policy, 2004)

Cradle-to-gate life cycle inventory and assessment of pharmaceutical compounds - Conceptión Jiménez-González; Alan D. Curzons; David J. C. Constable; Virginia L. Cunningham (The International Journal of Life Cycle Assessment, 2004)

Externally Applied Cyclic Strain Regulates Localization of Focal Contact Components in Cultured Smooth Muscle Cells - James J. Cunningham; Jennifer J. Linderman; David J. Mooney (Annals of Biomedical Engineering, 2002)

exma: an X-linked insertional mutation that disrupts forebrain and eye development - David Cunningham; Qiang Xiao; Aurobindo Chatterjee; Kathleen Sulik; Diana Juriloff; Frederick Elder; Wilbur Harrison; Gabriele Schuster; Paul A. Overbeek; Gail E. Herman (Mammalian Genome, 2002)

(+)-ABA content and lipid deposition in interior spruce somatic embryos - Danielle Julie Carrier; Cheryl A. Bock; James E. Cunningham; David R. Cyr; David I. Dunstan (In Vitro Cellular & Developmental Biology - Plant, 1997)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)